Lean-Kaizen startup in panela production processes: the case of a trapiche - Eduin Dionisio Contreras Castañeda; Juan José Gordillo Galeano; Karol Juliana Olaya Rodríguez (Cogent Engineering, 2024)
AbstractThe non-centrifugal cane sugar (panela) subsector stands out in Colombia as one of the most important agro-businesses, with economic growth and projection for the export of its products. For its part, the application of the Lean-Kaizen philosophy has proven to be effective for organizations to achieve continuous improvement in quality and productivity. This paper exposes the implementation of the pillars of Kaizen for the improvement of the panela manufacturing process applied in an artisan mill (Trapiche) in the Santander region, Colombia. Through the case study methodological approach, a Trapiche was selected and its production process was studied in terms of waste, order and cleanliness, and standardization. The results evidenced the types of waste that occur throughout the panela production process, the current state of order and cleanliness, and the way in which the operations are carried out to obtain the finished product. With the implementation housekeeping program (5S) and the standardization of the operational procedures, the main waste, sources of dirt and the reduction of the time used for the manufacture of panela were eliminated. The Kaizen actions improved the order and cleanliness of the Trapiche by 63% and the panela manufacturing time by 10%, complying with product quality standards.